The Act Protection for Islamic Banks in Financing Land and Rubber Plantation Ownership - Tektona, Rahmadi Indra; Ochtorina Susanti, Dyah; Helmi Septianto, Dea (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
Islamic banks in channeling funds to the public with two types, namely financing with the profit sharing system and financing with the sale and purchase system with deferred payment. Revenue sharing system is a system that includes procedures for the distribution of results of operations between the fund provider and the fund manager. The system of buying and selling with deferred payment is a system with profit margins, namely by implementing a system of buying and selling at a bank as a seller or by appointing a customer to be used as a bank agent to make purchases of goods and then selling the goods to customers at the agreed base price and profit. In practice, financing through Islamic banks does not rule out the possibility of problems, such as defaults such as the case in the Muara Enim Religious Court.